The Predatory Paradox: Ethics, Politics, and Practices in Contemporary Scholarly Publishing - Amy Koerber; Karin Ardon-Dryer; R. Glenn Cummins; Lyombe Eko; Kerk Kee (Open Book Publishers, 2023)
In today's 'publish or perish' academic setting, the institutional prizing of quantity over quality has given rise to and perpetuated the dilemma of predatory publishing. Upon a close examination, however, the definition of 'predatory' itself becomes slippery, evading neat boxes or lists which might seek to easily define and guard against it. This volume serves to foreground a nuanced representation of this multifaceted issue. In such a rapidly evolving landscape, this book becomes a field guide to its historical, political, and economic aspects, presenting thoughtful interviews, legal analysis and original research. Case studies from both European-American and non-European-American stakeholders emphasize the worldwide nature of the challenge faced by researchers of all levels. This coauthored book is structured into both textual and supplemental materials. Key takeaways, discussion questions, and complete classroom activities accompanying each chapter provide opportunities for engagement and real-world applications of these concepts. Crucially relevant to early career researchers and the senior faculty, library scholars, and administrators who mentor and support them, 'The Predatory Paradox: Ethics, Politics, and Practices in Contemporary Scholarly Publishing' offers practical recommendations for navigating the complex and often contradictory advice currently available. University instructors and teaching faculty will also find the reading essential in order to properly prepare both graduate and undergraduate students for the potential pitfalls endemic to scholarly publishing.
Keywords: 070; predatory publishing; scholarly ethics; scholarly politics; scholarly practices; universities; scholarly publishing